Proposal to improve commercial management to increase the profitability of a hotel company - Alfaro Rosas, Jorge Luis (LACCEI, 2024)
This study focuses on developing a proposal to improve commercial management and increase the profitability of a hotel. To achieve this objective, a cross-sectional descriptive methodology was adopted, using surveys as a data collection technique applied to a sample of personnel. Initially, a diagnosis was carried out using tools such as the problem prioritization matrix, which identified the low level of profitability as the main challenge, followed by the identification of underlying causes using the Ishikawa Diagram and the Pareto Law. Furthermore, the current situation was evaluated (AS-IS) and the desired situation was designed (TO BE). Using the Value Comparison Matrix, proposals were evaluated in terms of cost, quality, ease of implementation, customer service and time, considering the proposed solution of developing one’s own website. This solution is supported by a mathematical model implemented in Lingo to maximize the hotel’s occupancy and profit, which shows an increase in room occupancy of 85%, compared to the current 50%, which will increase the hotel’s profitability by 40.49 % to 50%, representing an improvement of 23%. The study concludes with an economic viability analysis that ensures the sustainability of the project under a Smart approach